2012
DOI: 10.1242/jeb.070110
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic scope and cardiovascular oxygen transport is not compromised at high temperatures in the toadRhinella marina

Abstract: SUMMARYNumerous recent studies convincingly correlate the upper thermal tolerance limit of aquatic ectothermic animals to reduced aerobic scope, and ascribe the decline in aerobic scope to failure of the cardiovascular system at high temperatures. In the present study we investigate whether this ʻaerobic scope modelʼ applies to an air-breathing and semi-terrestrial vertebrate Rhinella marina (formerly Bufo marinus). To quantify aerobic scope, we measured resting and maximal rate of oxygen consumption at temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 61 publications
6
49
3
Order By: Relevance
“…Given that neither VȮ 2 nor glucose concentration plateaued at high temperatures and that lactate concentration did not escalate with temperature, these snakes are not limited by oxygen acquisition or transport at temperatures near their thermal maximum. This result is in accordance with recent studies that refute the OCLTT hypothesis in free-living stages of terrestrial ectotherms (Fobian et al, 2014;He et al, 2013;McCue and Santos, 2013;Overgaard et al, 2012; but see Shea et al, 2016). Our data do not address other possible mechanisms that may contribute to thermal tolerance limits, including protein denaturation, membrane fluidity, enzymesubstrate interactions, mitochondrial failure and failure of neural processes (reviewed in Angilletta, 2009;Schulte, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Given that neither VȮ 2 nor glucose concentration plateaued at high temperatures and that lactate concentration did not escalate with temperature, these snakes are not limited by oxygen acquisition or transport at temperatures near their thermal maximum. This result is in accordance with recent studies that refute the OCLTT hypothesis in free-living stages of terrestrial ectotherms (Fobian et al, 2014;He et al, 2013;McCue and Santos, 2013;Overgaard et al, 2012; but see Shea et al, 2016). Our data do not address other possible mechanisms that may contribute to thermal tolerance limits, including protein denaturation, membrane fluidity, enzymesubstrate interactions, mitochondrial failure and failure of neural processes (reviewed in Angilletta, 2009;Schulte, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…_ V E was affected by temperature from 25 to 35°C (127% increase, Q 10 =2.27), mainly as a result of increases in V T (Q 10 =1.57). Thus, increased _ V E at high temperature matches an elevated metabolic rate up to 105% (thermal interval range from 25 to 35°C) reported in a closely related species, R. marina (Overgaard et al, 2012). High temperature exposure (35°C) in R. schneideri elicited cardiovascular adjustments to support an increased metabolic demand in which baseline f H rose 100% relative to that at 25°C, while blood pressure remained unchanged.…”
Section: Temperature Effects On Cardiorespiratory Reflex Responsessupporting
confidence: 66%
“…Such evidence is required when investigating a role for oxygen in thermal limitation. A later study of the same species by Overgaard et al (2012) found a typical exponential increase in resting oxygen consumption, which entered the steep phase beyond 30°C, in line with a transition to pejus range (see Fig. 2).…”
Section: Evolutionary Modulation Of Oclttmentioning
confidence: 54%